Long-term effects of fire and logging on groundwater table and soil moisture in Acacia plantation peatlands - Qalbi, Andria Harfani; Tarigan, Suria Darma; Barus, Baba; Sudadi, Untung (Journal of Degraded and Mining Lands Management, 2026)
Soil moisture and the groundwater tables are important for the sustainable management and maintenance of tropical peatland ecosystems. This study examined the long-term impacts of fires and logging on groundwater tables and soil moisture in peatlands used for Acacia plantations. Four land conditions were compared: natural forest (FRS), unharvested Acacia plantations (UHV), post-harvest areas in 2016 (HV), and post-fire areas in 2015 (BAR). Observations were made during the rainy and dry seasons to determine how peat responded to rainfall. The soil conditions observed included groundwater levels measured by the gravimetric method and dipwells, and other soil properties such as bulk density, soil porosity, and water-filled pore space. The results showed that natural forest and unharvested Acacia sites experienced increased soil moisture content during the wet season and a shallower groundwater table than the burned area, which consistently recorded the lowest values. All sites experienced a dramatic decline in both groundwater table and soil moisture during the dry season. This decline was most severe in post-fire peatlands, where the groundwater table fell by more than 80 cm and soil moisture declined from 389% to 230% in some locations. Statistical tests confirmed that both burning and logging had a significant effect on the physical characteristics of peat and groundwater table (? = 0.05). This study shows that, after many years, burned and harvested peatlands continue to experience hydrological degradation and are unable to maintain stable groundwater tables and soil moisture.